A special coating for steel structure resistant to seawater and salt spray corrosion and preparation method thereof

By using hybrids of zinc-aluminum hydrotalc and graphene and carboxymethyl cellulose in steel coatings, a multi-stage structure is formed, which solves the lack of wear resistance and corrosion resistance of steel structures in marine environments. The problem has significantly improved the adhesion of the paint, salt spray and salt water resistance, and extended its service life.

CN118165616BActive Publication Date: 2024-12-24河南宣垣新材料科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410333306.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2024-12-24
Estimated Expiration
2044-03-22

AI Technical Summary

Technical Problem

The existing anti-corrosion treatment methods in marine environments have problems such as excessive temperature, oxidation deformation, smoke pollution, insufficient wear resistance of the coating and poor corrosion resistance, resulting in low service life and unsuitable for large-area workpiece treatment.

Method used

Special steel coatings composed of epoxy resin, defoaming agent, anticorrosion filler, silane coupling agent, silicone leveling agent, curing agent and titanium dioxide are used to prepare hybrids of zinc-aluminum hydrotalcite and graphene as anticorrosion The filler, combined with carboxymethylcellulose modification, forms a multi-stage structure to improve the hydrophobicity and adhesion of the coating.

Benefits of technology

It significantly reduces the corrosion potential of the steel structure, improves the self-cleaning ability and adhesion of the coating, extends the service life, and enhances the salt spray and salt water resistance in the marine environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a special coating for steel structure resistant to seawater and salt spray corrosion and a preparation method thereof, comprising the following components: epoxy resin, defoamer, anticorrosive filler, silane coupling agent, silicone leveling agent, curing agent, active diluent and titanium dioxide. The anticorrosive filler in the coating is zinc-aluminum hydrotalcite and graphene hybrid, which can promote their respective dispersibility, and the multi-level structure greatly increases the "maze-like" anticorrosion effect; after being modified by carboxymethyl cellulose, the dispersibility and compatibility of zinc-aluminum hydrotalcite and graphene hybrid in the coating are greatly improved; the anticorrosive filler contains a large amount of hydroxyl groups, which can make the coating formed by the coating firmly adhere to the surface of the steel structure and inhibit the shedding of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating preparation, and in particular relates to a special coating for steel structures which is resistant to seawater and salt spray corrosion and a preparation method thereof. Background Art

[0002] The marine environment is often characterized by high rainfall, high temperature, much salt fog and strong winds. Offshore and marine engineering equipment are in the marine environment for a long time. The exposed parts will be subject to strong atmospheric corrosion, electrochemical corrosion and air flow erosion, which will cause the service life of various steel structure components to be much lower than that in general inland outdoor environments.

[0003] At present, the surface of steel structures is mainly treated with anti-corrosion by hot-dip coating or by directly spraying anti-corrosion coatings. When using hot-dip coating, the metal surface temperature may be too high and oxidative deformation may occur during the treatment process, and smoke, dust, and hot metal steam may cause serious pollution during operation. Such treatment methods may cause the surface of the steel structure to have insufficient wear resistance and weak erosion resistance. They are not suitable for large-area workpiece processing and field operations, which limits their application.

[0004] The existing steel structure treatment method is to spray multiple layers of anti-corrosion coating on the surface of the steel structure for anti-corrosion treatment to resist marine climate conditions. However, due to the extremely harsh marine climate conditions and the coating's own performance, the surface protective layer of the anti-corrosion coating is prone to cracking and falling off. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a special coating for steel structure which is resistant to seawater and salt spray corrosion and a preparation method thereof.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A special coating for steel structures which is resistant to seawater and salt spray corrosion. The raw materials thereof are composed of the following proportions by weight: 35-55 parts of epoxy resin, 0.8-1.8 parts of defoaming agent, 4-10 parts of anticorrosive filler, 2-4 parts of silane coupling agent, 1-3 parts of organosilicon leveling agent, 3-7 parts of curing agent, 5-15 parts of active diluent and 2-4 parts of titanium dioxide.

[0008] Furthermore, the raw material composition is as follows in proportion by weight: 45 parts of epoxy resin, 1.3 parts of defoaming agent, 7 parts of anticorrosive filler, 3 parts of silane coupling agent, 2 parts of silicone leveling agent, 5 parts of curing agent, 10 parts of active diluent and 3 parts of titanium dioxide.

[0009] Furthermore, the anticorrosive filler is prepared by the following steps:

[0010] Step 1: preparing a mixed solution A of sodium hydroxide and sodium carbonate; preparing a mixed solution B of zinc nitrate hexahydrate and aluminum nitrate nonahydrate;

[0011] Step 2: Take deionized water and add graphene oxide for ultrasonic dispersion, then add citric acid and continue ultrasonication, adjust the pH value to 10±0.1 with the mixed solution A and stabilize for 10 minutes to obtain solution C;

[0012] Step 3: adding the mixed solution A and the mixed solution B to the solution C obtained in step 2 at a stable pH value to carry out a crystallization reaction, then centrifugally washing with water until the pH of the washing solution is neutral, and then filtering and drying to obtain a hybrid of zinc-aluminum hydrotalcite and graphene;

[0013] Step 4: Dissolve carboxymethyl cellulose in an acetone aqueous solution, add a hybrid of zinc-aluminum hydrotalcite and graphene, reflux and dry, and then obtain an anti-corrosion filler.

[0014] Furthermore, the reaction temperature of the crystallization reaction in step 3 is 65° C., and the reaction time is 4 h.

[0015] Furthermore, the mass fraction of acetone in the acetone aqueous solution in step 4 is 60%.

[0016] Furthermore, the active diluent is any one of diglycidyl ether, triglycidyl isocyanate and glycerol epoxy.

[0017] Furthermore, the curing agent is any one of phthalic anhydride, isophorone diamine, and meta-xylene diamine.

[0018] A method for preparing a special coating for steel structure that is resistant to seawater and salt spray corrosion comprises the following steps: evenly mixing epoxy resin, anticorrosive filler, silane coupling agent, organic silicon leveling agent, active diluent titanium dioxide and defoaming agent, then adding a curing agent and mixing thoroughly to obtain a special coating for steel structure that is resistant to seawater and salt spray corrosion.

[0019] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0020] 1. Graphene has a high electron mobility, which can enrich electrons on the metal surface, thereby reducing the corrosion potential of the metal; in the hybrid of zinc-aluminum hydrotalcite and graphene, zinc-aluminum hydrotalcite can act as a sacrificial anode to slow down the corrosion rate of the steel structure, improve the hydrophobicity of the coating, reduce the effect of moisture in the external environment of the steel structure on the coating on the surface of the steel structure, extend the service life of the steel structure and the coating on the surface of the steel structure, and improve the self-cleaning ability of the coating on the surface of the steel structure. The hybrid of zinc-aluminum hydrotalcite and graphene contains a large amount of hydroxyl groups, which can make the coating firmly adhere to the surface of the steel structure, thereby inhibiting the shedding of the coating on the surface of the steel structure.

[0021] 2. After hybridization, zinc-aluminum hydrotalcite and graphene form a multi-level structure. The number of material layers is increased on the basis of the layered structure of hydrotalcite and graphene, which greatly enhances the "maze-like" anti-corrosion effect. At the same time, the dispersibility of zinc-aluminum hydrotalcite and graphene is significantly improved after hybridization, avoiding the aggregation of zinc-aluminum hydrotalcite and graphene.

[0022] 3. The dispersibility and compatibility of the hybrid of zinc-aluminum hydrotalcite and graphene in the coating are greatly improved after being modified by carboxymethyl cellulose. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In the following embodiments, the defoamer is the silicone defoamer BYK-065, the silane coupling agent is 3-glycidyloxypropyltrimethoxysilane, and the silicone leveling agent is MONENG-1070.

[0025] Example 1

[0026] A special coating for steel structures which is resistant to seawater and salt spray corrosion, wherein the raw materials thereof are composed in the following proportions by weight: 35 parts of epoxy resin, 0.8 parts of defoaming agent, 4 parts of anticorrosive filler, 2 parts of silane coupling agent, 1 part of organosilicon leveling agent, 3 parts of curing agent, 5 parts of active diluent and 2 parts of titanium dioxide.

[0027] The anticorrosive filler is prepared by the following steps:

[0028] Step 1: Dissolve 2.56g of sodium hydroxide and 2.12g of sodium carbonate in deionized water to prepare 200ml of mixed solution A; dissolve 4.46g of zinc nitrate hexahydrate and 2.23g of aluminum nitrate nonahydrate in deionized water to prepare mixed solution B;

[0029] Step 2: Add 0.05 g of graphene oxide to 100 ml of deionized water and ultrasonically disperse for 25 min, then add 0.02 g of citric acid and continue ultrasonication for 5 min, adjust the pH value to 10±0.1 with mixed solution A and stabilize for 10 min to obtain solution C;

[0030] Step 3: Add mixed solution A and mixed solution B to solution C in step 2 simultaneously, maintain the pH value of the solution at 10±0.1 during the dropping process, incubate at 65° C. for 4 hours after the dropping is completed, centrifuge and wash with water until the pH value of the washing solution is 7, filter and dry to obtain a hybrid of zinc-aluminum hydrotalcite and graphene;

[0031] Step 4: Dissolve 0.25 g of carboxymethyl cellulose in 100 ml of acetone aqueous solution with a mass fraction of 60% acetone, add 5 g of a hybrid of zinc-aluminum hydrotalcite and graphene, reflux for 3 hours, filter and dry, and then obtain an anti-corrosion filler.

[0032] The active diluent is bisglycidyl ether.

[0033] The curing agent is phthalic anhydride.

[0034] A method for preparing a special coating for steel structure that is resistant to seawater and salt spray corrosion comprises the following steps: evenly mixing epoxy resin, anticorrosive filler, silane coupling agent, organic silicon leveling agent, active diluent titanium dioxide and defoaming agent, then adding a curing agent and mixing them thoroughly to obtain a special coating for steel structure that is resistant to seawater and salt spray corrosion.

[0035] Example 2

[0036] A special coating for steel structures which is resistant to seawater and salt spray corrosion, wherein the raw materials are composed of the following proportions by weight: 45 parts of epoxy resin, 1.3 parts of defoaming agent, 7 parts of anticorrosive filler, 3 parts of silane coupling agent, 2 parts of organosilicon leveling agent, 5 parts of curing agent, 10 parts of active diluent and 3 parts of titanium dioxide.

[0037] The preparation method of the anti-corrosion filler is as described in Example 1.

[0038] The active diluent is triglycidyl isocyanate.

[0039] The curing agent is isophorone diamine.

[0040] The preparation method of a special coating for steel structure that is resistant to seawater and salt spray corrosion is the same as that of Example 1.

[0041] Example 3

[0042] A special coating for steel structures which is resistant to seawater and salt spray corrosion, wherein the raw materials are composed of the following proportions by weight: 55 parts of epoxy resin, 1.8 parts of defoaming agent, 10 parts of anticorrosive filler, 4 parts of silane coupling agent, 3 parts of organosilicon leveling agent, 7 parts of curing agent, 15 parts of active diluent and 4 parts of titanium dioxide.

[0043] The preparation method of the anti-corrosion filler is as described in Example 1.

[0044] The active diluent is glycerol epoxy.

[0045] The curing agent is m-xylene diamine.

[0046] The preparation method of a special coating for steel structure that is resistant to seawater and salt spray corrosion is the same as that of Example 1.

[0047] Comparative Example 1

[0048] A special coating for steel structures which is resistant to seawater and salt spray corrosion, wherein the raw materials are composed of the following proportions by weight: 45 parts of epoxy resin, 1.3 parts of defoaming agent, 7 parts of anticorrosive filler, 3 parts of silane coupling agent, 2 parts of organosilicon leveling agent, 5 parts of curing agent, 10 parts of active diluent and 3 parts of titanium dioxide.

[0049] The preparation method of the anticorrosive filler is as follows:

[0050] Step 1: Dissolve 2.56 g of sodium hydroxide and 2.12 g of sodium carbonate in deionized water to prepare 200 ml of mixed solution A; dissolve 4.46 g of zinc nitrate hexahydrate and 2.23 g of aluminum nitrate nonahydrate in deionized water to prepare mixed solution B;

[0051] Step 2: Add 100 ml of deionized water to a 500 ml four-necked flask, adjust the pH value to 10±0.1 with mixed solution A and stabilize for 10 min, then drop mixed solution A and mixed solution B simultaneously, maintain the solution pH value at 10±0.1 during the dropwise addition, incubate at 65° C. for 4 h after the dropwise addition, centrifuge and wash with water until the washing solution pH = 7, filter and dry to obtain zinc-aluminum hydrotalcite;

[0052] Step 3: Dissolve 0.25 g of carboxymethyl cellulose in 100 ml of acetone aqueous solution with a mass fraction of 60% acetone, add 5 g of the zinc-aluminum hydrotalcite prepared in step 2, reflux for 3 hours, filter and dry, and you can get the anti-corrosion filler.

[0053] The active diluent is triglycidyl isocyanate.

[0054] The curing agent is isophorone diamine.

[0055] The preparation method of a special coating for steel structure that is resistant to seawater and salt spray corrosion is the same as that of Example 1.

[0056] Comparative Example 2

[0057] A special coating for steel structures which is resistant to seawater and salt spray corrosion, wherein the raw materials are composed of the following proportions by weight: 45 parts of epoxy resin, 1.3 parts of defoaming agent, 7 parts of anticorrosive filler, 3 parts of silane coupling agent, 2 parts of organosilicon leveling agent, 5 parts of curing agent, 10 parts of active diluent and 3 parts of titanium dioxide.

[0058] The preparation method of the anticorrosive filler is as follows:

[0059] Dissolve 0.25 g of carboxymethyl cellulose in 100 ml of an acetone aqueous solution having an acetone mass fraction of 60%, add 5 g of graphene oxide, reflux for 3 hours, filter and dry, and then obtain an anticorrosive filler.

[0060] The active diluent is triglycidyl isocyanate.

[0061] The curing agent is isophorone diamine.

[0062] The preparation method of a special coating for steel structure that is resistant to seawater and salt spray corrosion is the same as that of Example 1.

[0063] Comparative Example 3

[0064] A special coating for steel structures which is resistant to seawater and salt spray corrosion, wherein the raw materials are composed of the following proportions by weight: 45 parts of epoxy resin, 1.3 parts of defoaming agent, 7 parts of anticorrosive filler, 3 parts of silane coupling agent, 2 parts of organosilicon leveling agent, 5 parts of curing agent, 10 parts of active diluent and 3 parts of titanium dioxide.

[0065] The preparation method of the anticorrosive filler is as follows:

[0066] Step 1: Dissolve 2.56g of sodium hydroxide and 2.12g of sodium carbonate in deionized water to prepare 200ml of mixed solution A; dissolve 4.46g of zinc nitrate hexahydrate and 2.23g of aluminum nitrate nonahydrate in deionized water to prepare mixed solution B;

[0067] Step 2: Add 100 ml of deionized water to a 500 ml four-necked flask, adjust the pH value to 10±0.1 with solution A and stabilize it for 10 minutes, then add mixed solution A and mixed solution B dropwise at the same time, maintaining the solution pH value at 10±0.1 during the addition process. After the addition is completed, incubate at 65°C for 4 hours, wash with water by centrifugation until the washing solution pH = 7, filter and dry to obtain zinc-aluminum hydrotalcite as the anti-corrosion filler.

[0068] The active diluent is triglycidyl isocyanate.

[0069] The curing agent is isophorone diamine.

[0070] The preparation method of a special coating for steel structure that is resistant to seawater and salt spray corrosion is the same as that of Example 1.

[0071] Comparative Example 4

[0072] A special coating for steel structures which is resistant to seawater and salt spray corrosion, wherein the raw materials are composed of the following proportions by weight: 45 parts of epoxy resin, 1.3 parts of defoaming agent, 7 parts of anticorrosive filler, 3 parts of silane coupling agent, 2 parts of organosilicon leveling agent, 5 parts of curing agent, 10 parts of active diluent and 3 parts of titanium dioxide.

[0073] The anti-corrosion filler is graphene oxide.

[0074] The active diluent is triglycidyl isocyanate.

[0075] The curing agent is isophorone diamine.

[0076] After forming the coating, the samples in the above embodiments and comparative examples were tested for adhesion, neutral salt spray resistance and salt water resistance (5wt% NaCl), and the results were as follows:

[0077]

[0078]

[0079] Zinc-aluminum hydrotalcite and graphene oxide can promote each other's dispersion after hybridization. According to the data in the attached table, according to Example 2, Comparative Example 1 and Comparative Example 2, when the anti-corrosion fillers each use zinc-aluminum hydrotalcite and graphene as the main raw materials, it can be found from Comparative Example 1 and Comparative Example 2 that the adhesion of zinc-aluminum hydrotalcite and graphene in water through carboxymethyl cellulose is 16.24Mpa and 15.34Mpa respectively as anti-corrosion fillers in the coating layer, which is significantly lower than the adhesion of the coating on the metal surface in water after the zinc-aluminum hydrotalcite and graphene are hybridized. The dispersibility of the anti-corrosion fillers zinc-aluminum hydrotalcite and graphene in the present invention is significantly improved after hybridization. At the same time, after the zinc-aluminum hydrotalcite and graphene oxide are hybridized, the neutral salt spray and salt water resistance of the steel structure surface coating in the marine environment are significantly improved.

[0080] The hybrid of zinc-aluminum hydrotalcite and graphene can be better dispersed in epoxy resin after being modified with carboxymethyl cellulose. From the comparison between Comparative Example 1 and Comparative Example 3, and the adhesion on the metal surface in Comparative Example 2 and Comparative Example 4, it can be seen that the adhesion of graphene and zinc-aluminum hydrotalcite after each modification with carboxymethyl cellulose is higher than the adhesion of graphene and zinc-aluminum hydrotalcite as fillers on the metal surface alone. According to Example 2 and Comparative Examples 1 and 2, it is concluded that the adhesion of zinc-aluminum hydrotalcite and graphene as anti-corrosion fillers on the metal surface after hybridization under the modification of carboxymethyl cellulose is greater than the adhesion of zinc-aluminum hydrotalcite and graphene as anti-corrosion fillers on the metal surface under the modification of carboxymethyl cellulose.

[0081] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A special coating for steel structure resistant to seawater and salt spray corrosion, characterized in that: The raw material composition is as follows in parts by weight: 35-55 parts of epoxy resin, 0.8-1.8 parts of defoaming agent, 4-10 parts of anticorrosive filler, 2-4 parts of silane coupling agent, 1-3 parts of organic silicon leveling agent, 3-7 parts of curing agent, 5-15 parts of active diluent and 2-4 parts of titanium dioxide; The anticorrosive filler is prepared by the following steps: Step 1: preparing a mixed solution A of sodium hydroxide and sodium carbonate; preparing a mixed solution B of zinc nitrate hexahydrate and aluminum nitrate nonahydrate; Step 2: Take deionized water and add graphene oxide for ultrasonic dispersion, then add citric acid and continue ultrasonication, adjust the pH value to 10±0.1 with the mixed solution A and stabilize for 10 minutes to obtain solution C; Step 3: adding the mixed solution A and the mixed solution B to the solution C obtained in step 2 at a stable pH value to carry out a crystallization reaction, then centrifugally washing with water until the pH of the washing solution is neutral, and then filtering and drying to obtain a hybrid of zinc-aluminum hydrotalcite and graphene; Step 4: Dissolve carboxymethyl cellulose in an acetone aqueous solution, add a hybrid of zinc-aluminum hydrotalcite and graphene, reflux and dry, and then obtain an anti-corrosion filler.

2. The special coating for steel structure resistant to seawater and salt spray corrosion according to claim 1, characterized in that: The raw material composition is as follows in proportion by weight: 45 parts of epoxy resin, 1.3 parts of defoaming agent, 7 parts of anticorrosive filler, 3 parts of silane coupling agent, 2 parts of organosilicon leveling agent, 5 parts of curing agent, 10 parts of active diluent and 3 parts of titanium dioxide.

3. The special coating for steel structure resistant to seawater and salt spray corrosion according to claim 1 is characterized by: The reaction temperature of the crystallization reaction in step 3 is 65° C. and the reaction time is 4 h.

4. The special coating for steel structure resistant to seawater and salt spray corrosion according to claim 1 is characterized in that: The mass fraction of acetone in the acetone aqueous solution in step 4 is 60%.

5. The special coating for steel structure resistant to seawater and salt spray corrosion according to claim 1 or 2, characterized in that: The active diluent is any one of diglycidyl ether, triglycidyl isocyanate and glycerol epoxy.

6. The special coating for steel structure resistant to seawater and salt spray corrosion according to claim 1 or 2, characterized in that: The curing agent is any one of phthalic anhydride, isophorone diamine and meta-xylene diamine.

7. A method for preparing a special coating for steel structure resistant to seawater and salt spray corrosion according to any one of claims 1 to 6, characterized in that: The following steps are involved: After epoxy resin, anti-corrosion filler, silane coupling agent, organic silicon leveling agent, active diluent titanium dioxide and defoaming agent are uniformly mixed, curing agent is added and fully mixed to obtain a special coating for steel structure which is resistant to seawater and salt spray corrosion.

Citation Information

Patent Citations

  • High-strength water-resistant corrosion-resistant epoxy resin powder coating

    CN105315845A

  • Water-based coating containing graphene / zinc-aluminum hydrotalcite nano composition and preparation method thereof

    CN106995643A

  • Water-based graphene conductive anticorrosive coating and preparation method thereof

    CN111286258A

  • Water-based damping coating with antistatic property, corrosion resistance and flame retardant property as well as preparation method and application of water-based damping coating

    CN115109489A

  • Wood environment-friendly coating with good dispersibility and preparation method thereof

    CN116814128A